Characteristics and Technologies of Advanced CNC Systems - Minhat, Mohamad; Xu, Xun (IGI Global, 2008)
Computer Numerical Control (CNC) systems are the “backbones” of modern manufacturing industry. Tomorrow’s manufacturing world is to take a much distributed, decentralized and collaborated manner; the traces of all of them are already abundantly clear in some parts of the world. This new trend comes with a suite of new technologies and concepts. The key issues will be autonomous planning and decision making, process monitoring and control systems that can adjust automatically to changing conditions and requirements. Among the other issues are also on automatic and dynamic adaptability for managing changes at the physical machine level of control to the exact point of view. Interoperability is realized through a Plug-and-Play module in the CNC system. The input to the system could be CNC data regardless of what machine tools are to be used. Extensibility, interoperability, portability and scalability have their own interpretation of CNC system should be by defining. The extensibility is the ease with which a third party is able to add capabilities to software or hardware. Interoperability is the ability of two or more computer systems to exchange information and make use of it transparently. Portability is the ease with which applications software can be transferred to one environment from another, while maintaining its capabilities. Scalability is the ease with which an existing system’s performance can be increased or decreased changes in the application demand. In modern and advances controller atmosphere the terms defining the technologies and technical features are very vital and playing the important role such as open system, adaptable, interoperable, distributable or distributed system, reconfigurable and modular. In the coming subsection this paper will discuss the defining terms and technologies.